2003
DOI: 10.1046/j.1525-1497.2003.21105.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in initial treatment for clinically localized prostate cancer

Abstract: African Americans with more aggressive cancers were less likely to undergo radical prostatectomy and more likely to be treated conservatively. These treatment differences may reflect African Americans' greater likelihood for presenting with pathologically advanced cancer for which surgery has limited effectiveness. Among men with less aggressive cancers-the majority of cases-there were no racial differences in undergoing radical prostatectomy or radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 46 publications
6
56
0
Order By: Relevance
“…These differences corroborate findings of many studies [17,19]. Researchers have also noted that strong social support may contribute to treatment patterns that influence outcomes [2].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These differences corroborate findings of many studies [17,19]. Researchers have also noted that strong social support may contribute to treatment patterns that influence outcomes [2].…”
Section: Discussionsupporting
confidence: 86%
“…Many studies have found more advanced disease at diagnosis [17], while other studies show poorer survival in AA men compared with other racial groups [1]. Conversely, some studies report no differences in age and clinical stage at diagnosis between AA and Caucasian men in settings of equal access to health care [18] and similar overall mortality rates across racial groups after treatment [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators reported racial and ethnic disparities that persist after controlling for socioeconomic factors and access to medical care, and found that most cancer in this population is still detected by screening. 20,21 Patients at SFGH were no older on average than those at UCSF and younger than those in CaPSURE, suggesting that delayed diagnosis due to poor access to care does not likely explain a large part of the risk difference.…”
Section: Resultsmentioning
confidence: 98%
“…Sexual QOL between Japanese and American men with localized prostate cancer Ethnic comparisons of sexuality after prostate cancer treatment have been limited to studies of non-Hispanic whites, African-Americans, and Hispanics in the US [39]. Disparities in sexual function among Asian men treated for prostate cancer have not been fully explored.…”
Section: Defining Sexual Qol: Validated Instrumentsmentioning
confidence: 99%